PENGARUH MINAT MEMBACA TERHADAP PRESTASI BELAJAR IPS KELAS V SDN SE-GUGUS II KASIHAN BANTUL TAHUN AJARAN 2023/2024 - Nifki Lailatusahidah; Selly Rahmawati (STKIP Subang, 2024)
The aim of this research is to determine the influence of interest in reading on social studies learning achievement for class V of SDN in cluster II Kasihan, Bantul in the 2023/2024 academic year and to determine the contribution of interest in reading to social studies learning achievement in class V of SDN in cluster II Kasihan, Bantul in the academic year 2023/2024. The type of research used in this research is quantitative survey. The population of this study was 133 and the sample used was 100 class V students of SDN in cluster II Kasihan, Bantul for the 2023/2024 academic year who were selected based on Michael's issac table. Data collection techniques in this research used questionnaires and tests. The data analysis used is a simple linear regression test. The results of this research concluded that interest in reading had a positive and significant effect on social studies learning achievement in class V. This can be shown by obtaining a value of Fcount = 105,057 while Ftable = 3.94 with a significance value of 0.016. Therefore, it can be concluded that the p value is <0.05, which means that reject Ho with a value of 105,657 > 3.94. Interest in reading contributes to learning achievement by 51,9 and the rest is influenced by other factors.